2020
DOI: 10.1186/s13031-020-00290-0
|View full text |Cite
|
Sign up to set email alerts
|

No implementation without cultural adaptation: a process for culturally adapting low-intensity psychological interventions in humanitarian settings

Abstract: Background: Despite the widely recognised importance of cultural adaptation to increase the effectiveness of psychological interventions, there is little guidance on its process. Developed based on existing theory, we applied a four-step process to culturally adapt a low-intensity psychological intervention for use in humanitarian settings. Methods: The four-step process was applied to adapt a WHO low-intensity psychological intervention (i.e. Problem Management Plus, or PM+) for use with displaced Venezuelans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 47 publications
0
66
0
1
Order By: Relevance
“…Health system related barriers imply that mental health interventions in humanitarian crises need to be developed by taking these context-specific characteristics and fragilities of the systems into account to maximise scalability of the intervention. This can be ensured early on in the research process through adapting the intervention to the delivery systems and the populations it will serve [ 48 ]. Our review also identified a number of socio-economic and cultural factors compounded by crises that can further prevent people from accessing MHPSS services (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Health system related barriers imply that mental health interventions in humanitarian crises need to be developed by taking these context-specific characteristics and fragilities of the systems into account to maximise scalability of the intervention. This can be ensured early on in the research process through adapting the intervention to the delivery systems and the populations it will serve [ 48 ]. Our review also identified a number of socio-economic and cultural factors compounded by crises that can further prevent people from accessing MHPSS services (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although an existing cultural adaptation methodology has been presented to adapt individual PM+ with refugee populations (Perera et al ., 2020 ), our approach has several advantages including a central focus on the processes that lead to change (i.e. mechanisms of action), attention to implementation parameters beyond content modification (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have recommended the decentralization of mental health services, provision of integrated and holistic care within primary health care and communities, and the strengthening of health systems [6,7] to redress key barriers to GMH implementation. Ensuring the appropriateness of mental health interventions through formative research to understand and incorporate culturally and contextually appropriate approaches to mental health, well-being and recovery have also been identified as important considerations for successful mental health service delivery [8][9][10].…”
Section: Introductionmentioning
confidence: 99%